Modulation of the nutritional value of lupine wholemeal and protein isolates using submerged and solid‐state fermentation with Pediococcus pentosaceus strains. (26th March 2018) - Bartkiene, Elena; Sakiene, Vytaute; Bartkevics, Vadims; Juodeikiene, Grazina; Lele, Vita; Wiacek, Claudia; Braun, Peggy G.
Summary: The influence of different factors (submerged and/or solid‐state fermentation, pediococci strain, lupine variety and protein isolation process) on the protein digestibility, total phenolic compounds (TPC) content and radical scavenging activity of Lupinus luteus and angustifolius wholemeal and protein isolates was evaluated. As safety factor, biogenic amines (Bas) formation was analysed. The Pediococcus pentosaceus strains No. 8, No. 9 and No. 10 are suitable starters for lupine wholemeal fermentation and both applied processes (fermentation and protein isolation) increase protein digestibility (by 10%). Higher TPC content in fermented wholemeal can be obtained, compare to isolates. In SMF isolates by 58.3%, 68.2%, 95.6%, 76.6%, lower content of phenylethylamine, putrescine, cadaverine and histamine, respectively was found. The highest protein digestibility and the lowest BAs content using submerged fermentation with pediococcus No. 8 in lupine variety Vilnius protein isolates can be obtained and this technology for high‐quality lupine proteins preparation can be recommended. Abstract : Modulation of the nutritional value of lupine wholemeal and protein isolates using submerged and solid‐state fermentation with Pediococcus pentosaceus strains.